2006
DOI: 10.1175/bams-87-12-1727
|View full text |Cite
|
Sign up to set email alerts
|

Probing Finescale Dynamics and Microphysics of Clouds with Helicopter-Borne Measurements

Abstract: A new helicopter payload designed to overcome rotor downwash allows better than 10 cm resolution for turbulence and microphysical observations in boundary layer clouds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 21 publications
7
102
0
Order By: Relevance
“…ACTOS is attached to the helicopter by means of a 140 m long rope to avoid any influence from the rotor downwash and its typical true airspeed is about 15 m s −1 enabling high-resolution measurements in the cloudy atmosphere. A detailed description of the ACTOS payload and its general performance is given in Siebert et al (2006a). The analysis of this work is mainly based on measurements of the three-dimensional wind vector measured with an ultra-sonic anemometer (hereafter called "sonic"), Solent HS (Gill Instruments, Lymington, UK), the liquid water content (LW C) measured with a particle volume monitor (PVM-100A; Gerber et al 1994), the temperature (T ) measured with a special cloud thermometer (UltraFast Thermometer, UFT, Haman et al 1997), the absolute humidity (a) measured with an open-pass infrared absorption hygrometer (Licor, LI-7500) and the number concentration of interstitial aerosol (N ) measured with a condensation particle counter (CPC, model 3762A, TSI Inc., St. Paul, Minnesota, USA).…”
Section: Methodsmentioning
confidence: 99%
“…ACTOS is attached to the helicopter by means of a 140 m long rope to avoid any influence from the rotor downwash and its typical true airspeed is about 15 m s −1 enabling high-resolution measurements in the cloudy atmosphere. A detailed description of the ACTOS payload and its general performance is given in Siebert et al (2006a). The analysis of this work is mainly based on measurements of the three-dimensional wind vector measured with an ultra-sonic anemometer (hereafter called "sonic"), Solent HS (Gill Instruments, Lymington, UK), the liquid water content (LW C) measured with a particle volume monitor (PVM-100A; Gerber et al 1994), the temperature (T ) measured with a special cloud thermometer (UltraFast Thermometer, UFT, Haman et al 1997), the absolute humidity (a) measured with an open-pass infrared absorption hygrometer (Licor, LI-7500) and the number concentration of interstitial aerosol (N ) measured with a condensation particle counter (CPC, model 3762A, TSI Inc., St. Paul, Minnesota, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The Taylor-scale Reynolds number, R λ , varies correspondingly between stratocumulus and cumulus: R λ ∼ 5000 in stratocumulus (Siebert et al, 2010a) and R λ ∼ 30 000-40 000 in cumulus (Siebert et al, 2006a). These values of ε can be misleading in that they give no indication of the extremely large fluctuations in the local dissipation rate that are possible: for example, in small cumulus clouds Siebert et al (2006b) found that the dissipation rate could vary by a factor of 50 over scales of order 15 m (see Figure 5 therein); Meischner et al (2001) also found that the dissipation rate could vary by several orders of magnitude on scales of order 100 m within thunderstorm anvils.…”
Section: Cloud-scale Turbulencementioning
confidence: 99%
“…In addition, one might anticipate that the turbulence intensity should be highest near the cloud edge where turbulent entrainment and mixing between the cloudy air and subsaturated (and typically non-turbulent) air take place (e.g. Siebert et al, 2006aSiebert et al, , 2006b. Numerical simulations by Seifert et al (2010) show that ε reaches a maximum near the cloud top at its windward edge (see Figure 6 therein).…”
Section: Sources Of Cloud Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…The easternmost island in the Caribbean, Barbados, was used as a base to examine the interplay between undisturbed marine aerosol and warm clouds. Ground-based and airborne measurements were performed, where the measurement platform ACTOS (Airborne Cloud Turbulence Observation System; Siebert et al, 2006) was deployed for the latter. An overview of the measurement activities, which took place during the two periods of CAR-RIBA in November 2010 and April 2011, is given in Siebert et al (2013).…”
mentioning
confidence: 99%